Identifikasi Sikap Peserta Didik terhadap Mata Pelajaran Fisika di Sekolah Menengah Atas Negeri 5 Kota Jambi (UPEJ Unnes Physics Education Journal, 2019)
The aims of this research is to determine the student’s attitude in Sekolah Menengah Atas Negeri 5 Kota Jambi towards physics learning. This is quantitative study using survey design. This study involved 126 students from the Jambi 5 State High School. Data were collected through questionnaires as many as 54 statements and used a 5-point Likert scale and interviews as a reinforcer of the questionnaire. Data analysis used is descriptive statistical analysis. The results of the analysis obtained on the indicator of scientist normality are sufficient with a percentage of 50.0%. Scientific Normality Indicator with a percentage of 69.8% with the enough category. Indicators of attitude toward investigation of physics as many as 51.6% are sufficiently categorized. Based on these results in part at the Negeri 5 Senior High School in Jambi City students have a fairly good attitude towards learning physics